ART ANALYSIS AS A DIAGNOSTIC TOOL IN ART THERAPY - Rakhmatova Iqbolkhon Inomjonovna,; Narzilloeva Mahvash Davlatbekovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Art therapy has become an increasingly important field within modern psychology and psychotherapy due to its ability to provide non-verbal channels for emotional expression and psychological assessment. Among its many techniques, drawing analysis stands out as a valuable diagnostic tool that allows therapists to explore the inner world of individuals. This article examines the theoretical foundations of art therapy and focuses on the role of visual art, particularly drawing, in diagnosing emotional and psychological conditions.